Desempenho operacional e energético do conjunto trator semeadora adubadora camalhoeira: adubação em milho consorciado e viabilidade econômica - Santos, Paulo Ricardo Alves dos (2020)
The use of machinery that allows at the same time the preparation of the soil to capture rainwater in situ and the sowing of crops in consortium (corn + fodder) with the fertilizer momentarily is an alternative of great importance in the conditions of semi-arid regions, because it favors the conservation of the soil, allowing the retention of water for longer in the soil, in addition to reducing the costs of field operations. Thus, in the present work, three studies were carried out, where the first aimed to evaluate the operational and energetic performance of a shrimp fertilizer spreader, in the use of six sowing systems: (S1 - sowing of corn in consortium on top of the ridge; S2 - sowing of corn in ridge without consortium; S3 - sowing of corn in consortium within the furrow; S4 - sowing of corn within the furrow without consortium; S5 - conventional sowing in consortium; S6 - conventional sowing without consortium) and two mechanisms for deposition of fertilizers (M1- disc mechanism and M2 - rod mechanism) in the factor scheme 6 x 2 with 4 repetitions. In the second study, the objective was to evaluate the corn crop production according to different sowing systems, mechanism for fertilizer deposition and different levels of nitrogen fertilization in mulch taking into account the needs of the crops in consortium. For this purpose, six sowing systems (S1, S2, S3, S4, S5 and S6), two mechanisms (M1- disc mechanism and M2 - rod mechanism) and four levels of nitrogen fertilization in mulch were used, (0; 60; 110 and 165 Kg/ha-1), making a factorial 6x2x4 with four repetitions. For the third study, the objective was to analyze, economically, the effect of the same factors of study II. The statistical analysis was performed using the SISVAR program at 5% of significance. It was possible to conclude that independent of the sowing system (camallion or furrow) and mechanism used, there is no difference in the initial population of corn plants and in the depth of seeds (corn and fodder). However, more attention is needed to the depth of fertilizer and fodder seed when momentarily deposited together. The sowing systems that mobilize the soil (furrow and ridge) present higher energy consumption, as well as the rod mechanism; The S5 sowing system presents better operational performance, together with the disc mechanism. For the second study, it was possible to conclude that the systems of sowing in camallion and furrow with the use of the mechanism stem favor the components of growth of the corn crop, already in relation to the productivity of grains, the systems of sowing in camallion is the most indicated, independent of the mechanism used; nitrogen fertilization in cover realized in function of the necessity of all the crops in consortium is promising alternative, because it increases linearly the components of the production and the productivity of the crop of corn in consortium with fodder. In the third study, it was concluded that the system in camalhão (S2) fertilized with the dose of 165 kg ha-1 of N in covering with the use of the rod mechanism favors greater profitability. However, it is not recommended the use of the S3 and S4 system without fertilization and with the use of the disc, because they promote lower rates of profitability and operational profit, favoring losses to producers.